Brief Analysis of Power Converters Standards for Rail Transit Rolling Stock - Ning ZHANG; Qiang WU; Yi ZHANG; Deng WEN (机车电传动)
The basic situation, correlation and differences of the standards related to power converters for rail transit locomotives and rolling stock were analyzed, the key terms and important parameters of some product standards was discussed, and the development trend of product standards was look forward, so as to provide reference for relevant personnel engaged in power converter industry.